Cutaneous immune‐related adverse events and photodamaged skin in patients with metastatic melanoma: could nicotinamide be useful?. (18th June 2022) - De Giorgi, Vincenzo; Colombo, Jacopo; Trane, Luciana; Silvestri, Flavia; Venturi, Federico; Zuccaro, Biancamaria; Doni, Laura; Stanganelli, Ignazio; Covarelli, Piero
Abstract: Cutaneous immune‐related adverse events (irAEs) occur in more than one‐third of patients treated with immune checkpoint inhibitors; they are often the first clinical manifestation, although they may occur months after initiation of therapy. We noticed that our patients usually have these cutaneous AEs on photodamaged skin. In fact, out of 19 patients being treated for metastatic melanoma, 8 (42%), all of whom had significant cutaneous actinic damage, developed cutaneous irAEs earlier and in a more serious form than those without such damage. Thus, we gave a high oral dose of nicotinamide (500 mg twice daily) to the patients with metastatic melanoma who had photodamaged skin, and continued this for the entire duration of the immunotherapy. The appearance of the first signs of cutaneous irAEs was 180 days after starting therapy in nicotinamide‐treated patients, compared with 65 days for patients not treated with nicotinamide.